2018
DOI: 10.1007/s10935-018-0509-8
|View full text |Cite
|
Sign up to set email alerts
|

How Mentor Support Interacts With Mother and Teacher Support in Predicting Youth Academic Adjustment: An Investigation Among Youth Exposed to Big Brothers Big Sisters of Canada Programs

Abstract: This study examines three potential contributions (i.e., additive only, hierarchical compensatory, and hierarchical conditional) of mentor support to youth academic adjustment, taking into account interactions with support from mothers and teachers. We derived data from a larger study of the Big Brothers Big Sisters (BBBS) of Canada community mentoring program. The sample included 427 youth (average age 9.8 years; 64% girls, 56% White) who received one-to-one community-based mentoring for at least three months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
0
12
1
1
Order By: Relevance
“…American mentees with better preexisting adult relationships and stronger family ties and school bonds established higher-quality relationships with their mentors in a short-term mentoring program [ 54 ]. Finally, mentors’ support predicted positive changes in the mentees’ academic adjustment following their participation in BBBS Canada, primarily when the mentees had already reported considerable support from their mothers [ 155 ]. These findings should encourage researchers to question the assumption that mentoring constitutes a corrective experience for mentees (i.e., the compensatory model) and underscore the need to involve parents in the mentoring process.…”
Section: Resultsmentioning
confidence: 99%
“…American mentees with better preexisting adult relationships and stronger family ties and school bonds established higher-quality relationships with their mentors in a short-term mentoring program [ 54 ]. Finally, mentors’ support predicted positive changes in the mentees’ academic adjustment following their participation in BBBS Canada, primarily when the mentees had already reported considerable support from their mothers [ 155 ]. These findings should encourage researchers to question the assumption that mentoring constitutes a corrective experience for mentees (i.e., the compensatory model) and underscore the need to involve parents in the mentoring process.…”
Section: Resultsmentioning
confidence: 99%
“…and micro-environment (family, teachers, peers, etc.). In the literature, identified factors that affect learning adjustment among high school students include environmental factors (e.g., family socioeconomic status, parenting style, teacher support, peer friendship, and social environment) (Hair and Graziano, 2003; Verner-Filion and Gaudreau, 2010; Butler, 2011; Garg et al, 2016) and individual factors (e.g., personality, intelligence, achievement motivation, and academic self-efficacy) (Powers et al, 2005; Gunnoe, 2013; Shin and Ryan, 2014; Larose et al, 2018). In all personal variables, researchers have found that shyness as a personality trait affected individuals’ learning adjustment (Chen et al, 1995; Liu et al, 2012; Yang et al, 2015; Coplan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Empathy is difficult to measure with questionnaires (Wieck & Kunzmann, 2015). A wide range of other social aspects have been investigated using self‐reports, like coping behavior (DeWit et al., 2016; Larose et al., 2018), relationships with parents (Grossman & Rhodes, 2002), or social support (Larose et al., 2018). Theoretical considerations and findings for related constructs would suggest that youth mentoring improves the prosocial behavior and empathy in children.…”
Section: Assessment Of Social–emotional and Cognitive Development In Mentoring Programsmentioning
confidence: 99%
“…Youth mentoring programs are becoming more and more common around the globe. As meta‐analyses confirmed their effectiveness over a wide range of domains (DuBois et al., 2002; DuBois et al., 2011; Durlak et al., 2011; Raposa et al., 2019), youth mentoring programs have been established all over the world, for example, in Rwanda (Brown et al., 2009), New Zealand (Farruggia et al., 2011), or Canada (Larose et al., 2018). The majority of studies evaluating mentoring effects rely mostly or solely on self‐reports of mentors and mentees (Pryce et al., 2020; Raposa et al., 2019).…”
mentioning
confidence: 97%